Effects on BBPS score with bowel preparation time and dosage. Issue 27 (8th July 2022) - Lu, Wei; Zhou, Kena; Cai, Congbo; He, Yi; Jiang, Honggang; Li, Xinke
Abstract : Background: To evaluate the effects on the Boston Bowel Preparation Scale (BBPS) score with different bowel preparation times and dosages. Methods: Six hundred patients who underwent colonoscopy in the Endoscopy Center of Ningbo No.9 Hospital in 2021 were recruited and randomly assigned to 3 groups: Group A: "4-hour 1 + 2L" bowel preparation regimen; Group B: "6-hour 1 + 2L" bowel preparation regimen; and Group C: "4-hour 0 + 2L" bowel preparation regimen. BBPS score among these groups is compared and analyzed in the Statistical Product and Service Solutions software. Results: There was no difference in baseline characteristics among the three groups of patients ( P > .05). There was no significant difference in the BBPS score between Group B and Group C, whereas the BBPS score in Group A was significantly higher than that in Groups B and C ( P < .05). Conclusion: The "4-hour 1 + 2L" bowel preparation regimen can obtain higher BBPS score for colonoscopy, which is suggested to be the optimal plan for colonoscopy patients of the time and dosage. Definitely, higher BBPS score can improve the quality of colonoscopy diagnosis and treatment consequence.